Do Internal Government Auditors (Always) Follow Audit Standards? A Case Study in Goverment Internal Auditor Office Chapter Aceh - Basri, Hasan; Fahlevi, Heru; Hastati, Sri (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
This study was aimed at measuring and evaluating the compliance of Aparat Pengawas Internal Pemerintah (or Government Internal Auditors, hereafter GIAs) on the used audit standards in Indonesia. This case study research was carried out in Aceh provincial GIA office. The data is collected from survey and semistructured interviews with key officers in the studied GIA office. To analyse and discuss the research findings, this paper employs the Milgram’s Obedience Theory (1963). This study found that most of the GIA follows the audit standards. However, there are two audit standards that mainly were not followed by the auditors i.e. the supervisor review of the produced Auditing Worksheet and timely completion of Audit Report. This study also found factors that determine of the obedience of GIAs to the audit standards, namely auditor responsibility, colleague/other audtior upports, competency of GIAs, organizational commitment, and task complexity.